Unintended consequences of drug policies experienced by young drug users in contact with the criminal justice systems - Moskalewicz, Jacek; Dąbrowska, Katarzyna; Herold, Maria Dich; Baccaria, Franca; Rolando, Sara; Herring, Rachel; Thom, Betsy; Kahlert, Rahel; Stummvoll, Günter; Moazen, Babak; Stöver, Heino; Pisarska, Agnieszka (Drugs, 2021)
The aim of this paper is to assess to what extent prohibitive drug policies hamper the management of drug problems from the perspective of young people who have experience with the criminal justice systems (CJS). Qualitative, in-depth interviews were carried out in six European countries (Austria, Denmark, Germany, Italy, Poland, and the UK) following a common interview guide to obtain comparative data on the life trajectories of drug experienced youth. Altogether 198 interviews with people aged 14-25 years were collected and analysed by national teams following a common coding book. Unintended consequences of drug policies for the individual and society were identified. Individual consequences included health consequences and traumatic experiences with law enforcement. Social consequences included those affecting social relations such as stigmatisation and those impacting on institutions, for example, focusing on drug use and neglecting other problems. This paper confirmed earlier research indicating unintended consequences of prohibitive drug policies but also added to the literature its cross-national perspective and use of young people narratives as a source of analyses. There are, however, policy measures available that may reduce the volume and range of unintended effects. Their implementation is crucial to reduce the array of unintended consequences of prohibitive drug policies.
Gesehen am 11.10.2021